Design Thinking-Based UI/UX Prototype for a Hospital Patient Registration Information System - Laila Hasanah; Berto Nadeak; A.M. Hatuaon Sihite (Divisi Riset, Lembaga Mitra Solusi Teknologi Informasi (L-MSTI), 2026)
The patient registration process is an important service in hospitals because it affects service efficiency and patient satisfaction. Although RSU Sari Mutiara Lubuk Pakam has implemented a patient registration system, several problems still occur, such as BPJS verification issues, inefficient queue management, and limited patient understanding of the registration process. This study aims to design a User Interface (UI) and User Experience (UX) prototype for a patient registration information system using the Design Thinking method. The research applied the five stages of Design Thinking: empathize, define, ideate, prototype, and test. Data were collected through observation, interviews, literature review, and questionnaires involving 50 respondents, including patients and registration staff. The prototype was designed using Figma and provides features such as patient type selection, BPJS and general patient verification, clinic and appointment scheduling, doctor schedule information, referral letter upload, e-ticket generation, and queue status monitoring. The prototype was evaluated using the System Usability Scale (SUS), resulting in an average score of 78.35. This score falls into the Acceptable category with a Grade B and an Excellent usability rating. The findings indicate that the proposed prototype is easy to use and can improve the efficiency and quality of the patient registration service at RSU Sari Mutiara Lubuk Pakam.